The role of HMGB1/RAGE in inflammatory cardiomyopathy - Volz, Hans Christian; Kaya, Ziya; Katus, Hugo; Andrassy, Martin (Seminars in thrombosis and hemostasis, 2010)
We propose that the interaction of HMGB1 and RAGE is a key component initiating and sustaining the inflammatory response in inflammatory cardiomyopathy eventually leading to heart failure. Thus HMGB1-antagonizing gene therapy represents a new therapeutic strategy...
Gesehen am 13.09.2023